Pembangkit Tegangan Tinggi Frekuensi Tinggi Kumparan Tesla untuk Generator Ozon - Annita Lubis; Sukardi Sukardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
Ozone is a compound that has many benefits and roles in the development of science and technology. Ozone can be used for sterilization, removing color, deodorizing, and breaking down organic compounds. Ozone can be generated by several methods, including plasma discharge and plasma dielectric barrier discharge (DBDP). In the plasma discharge method high voltage electricity is required to break down oxygen molecules into oxygen ions which will form ozone. High voltage can be generated by using a DC Tesla coil. The advantages of DC Tesla coil compared to other high voltage generators are that it can generate high voltages with a simple system, only requires a small space, and does not cost a lot of money. Based on experiments carried out the deposition of ozone which is generated by several factors, including ozonation time, oxygen flow rate, and high voltage.